The importance of activating the results of the Federal Boards of Supreme Audit and its role in combating corruption and achieving reform: An applied study on a sample of control reports from the Federal Boards of Supreme Audit (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The purpose of the research is to clarify the role of the follow-up phase of the results of the auditing and auditing activities carried out by the FBSA in the form of supervisory reports issued by it, which includes observations and violations in the activities of government departments and the public sector because it is one of the most important stages of the general control process touched society by raising the performance of these departments and to improve the level of public governance in the management of public funds and provide better services and strengthen public accountability, since no use of controls without follow-up results and take corrective action and Treatment needed to avoid deficiencies and weaknesses and deficiencies and ensure that they do not recur in the future, so we find that all senior oversight bodies have paid great attention to this stage despite the different legal legislation regulating its administrative, technical and legal competence is keen to establish themselves as a mission to protect public funds from waste and misconduct, and thus prove their importance and value and benefits in the community. The research has come to a set of conclusions are not parties subject to the control of the Bureau in response to the results of regulatory reports issued by him as well as a weakness in the legal mandate given to him in order to activate the results of those reports, andresearch found a set of recommendations is to give SAI legal terms of reference assist in the activation of the results of his reports with the activation of some legal materials contained in the law No. (31) of 2011 (as amended), as well as giving up the regulatoryreporting process space of the annual report to facilitate communication with stakeholders, including higher authorities, Which is reflected in the end result to combat corruption in its dangerous forms and to meet the requirements of the reform expected.